Persistent Malnutrition among Children under five in Pastoral Communities of Aweil Centre, South Sudan - Ratib, Dricile; Chakrabartty, Arupkumar; Kahuma Kabakyenga, Jerome (International Journal of Scientific Research and Management (IJSRM), 2023)
Malnutrition is one of the leading causes of morbidity and mortality among children globally, and has been linked to 60% of the 10.9M deaths annually of under-fives. High prevalence of infectious diseases contributes to malnutrition and vice versa making the situation even worse. In WHO’s African region, the median stunting prevalence is 31.3%.The worst scenarios are seen in the war tone countries; for example Aweil Center of South Sudan has consistently high malnutrition rates despite running nutrition projects by UN agencies, government and other partners with relative stability. Results from Survey carried out in 2013 indicated poverty levels  at 76%, severe acute malnutrition (SAM) prevalence rate of 6.3% (95% CI, 4.5-8.9), Global acute malnutrition (GAM) rate of 22.4% (95% CI, 17.8-27.7) with under five mortality rate of 152 deaths/ 1,000 live births.A cross-sectional study with two-stage cluster sampling method done to determine the associated factors of malnutrition among children 6-59 months in Aweil Center County. The results showed high burden of infectious diseases like fever, diarrhea, eye, skin  and respiratory tract infections at 94.5% with p-value 0.00022 (95%C.I, 0.1667-0.291). Very low household dietary diversity score of only 24 % (125out of 513 families). There was low coverage of primary health care interventions; e.g. Vitamin A, LLITN and measles vaccinations at 53%, 52.8% and 55% respectively. Accessibility to CBDs for iCCM associated with better nutrition status of children p-value 0.032 and OR 0.62 (95% CI 0.41-0.94). Poor feeding methods, family planning practices; and poor access roads to markets impact on nutrition status of children.Multifaceted approach is needed to root out the persistent malnutrition from Aweil Center: Shift from food aid to support of food production, scale up of primary health care and iCCM interventions to include IPT for malnourished children and community awareness on feeding practices and family planning